Industrial energy, materials and products: UK decarbonisation challenges and opportunities. (25th May 2018) - Barrett, John; Cooper, Tim; Hammond, Geoffrey P.; Pidgeon, Nick
Highlights: An interdisciplinary review is presented of industrial decarbonisation in the UK. Various socio-technical methods for analysing industrial energy use are explored. Materials content changes in manufacture products can lead to decarbonisation. The way that final consumers use products can also reduce energy demand. 2050 low carbon 'roadmaps' for some UK energy-intensive industries are presented. Abstract: The United Kingdom (UK) has placed itself on a transition pathway towards a low carbon economy and society, through the imposition of a legally-binding target aimed at reducing its 'greenhouse gas' (GHG) emissions by 80% by 2050 against a 1990 baseline. Reducing industrial energy demand could make a substantial contribution towards this decarbonisation goal, while simultaneously improving productivity and creating employment opportunities. Both fossil fuel and process GHG emissions will need to be significantly reduced by 2050. Ultimately, all industrial energy use and emissions result from the demand for goods and services. Energy is required at each stage in the manufacture of a product from raw material extraction through to the final distribution and eventual disposal. The required energy and associated GHG emissions along UK supply chains emanate from many different countries, due to the growth of globalisation. A range of socio-technical methods for analysing decarbonisation have therefore been explored. Efficiency gains can be made in industry, including those associated with the use of heat and with improvements in processing. Changes in the materials needed to manufacture products (via material substitution, light-weighting and ' circular economy ' interventions) can also lead to emissions reductions. Likewise, altering the way the final consumer (industry, households or government) use products, including through product longevity and shifts from goods to services, can further reduce energy demand. The findings of an interdisciplinary study of industrial decarbonisation is therefore reported. This gave rise to the identification of the associated challenges, insights and opportunities, in part stemming from the development of a novel set of 2050 decarbonisation 'technology roadmaps' for energy-intensive industries in the UK. These determinations provide a valuable evidence base for industrialists, policy makers, and other stakeholders. The lessons learned are applicable across much of the wider industrialised world.